Assessment of tumour‐associated necrosis provides prognostic information additional to World Health Organization/International Society of Urological Pathology grading for clear cell renal cell carcinoma. Issue 2 (17th October 2018) - Dagher, Julien; Delahunt, Brett; Rioux‐Leclercq, Nathalie; Egevad, Lars; Coughlin, Geoff; Dunglison, Nigel; Gianduzzo, Troy; Kua, Boon; Malone, Greg; Martin, Ben; Preston, John; Pokorny, Morgan; et al.
Abstract : Aims: The aims of this study were to evaluate the impact of tumour‐associated necrosis (TAN) on metastasis‐free survival for clear cell renal cell carcinoma (RCC), and to determine whether TAN provides survival information additional to World Health Organization (WHO)/International Society of Urological Pathology (ISUP) grading. Methods and results: The study consisted of 376 cases of clear cell RCC treated by nephrectomy, for which follow‐up was available. WHO/ISUP grade was assigned, and sections were assessed for the presence of TAN. American Joint Committee on Cancer (AJCC) pT staging category and tumour size were also recorded. The development of metastatic disease was taken as the clinical endpoint, and survival analyses, utilising univariate and multivariate models, were performed. WHO/ISUP grades were: grade 1, 35 cases (9.3%); grade 2, 188 cases (50.0%); grade 3, 91 cases (24.2%); and grade 4, 62 cases (16.5%). Staging categories were pT1–pT2 [234 tumours (62.2%)] and pT3–pT4 [139 tumours (37.0%)]. TAN was seen in 128 cases (34.0%). Neither TAN nor metastases were seen in grade 1 tumours. Among grade 2–4 tumours, those with TAN had a significantly worse prognosis than those without TAN ( P = 0.017, P = 0.04, and P = 0.006, respectively). Multivariate analysis (WHO/ISUP grade, pT staging category, and TAN) showed all three variables to be independently associated with outcome ( P = 0.009, P = 0.005, and P = 0.001, respectively). For all tumour grades and pT staging categories, it was found that the presence of TAN was associated with a 2.91‐fold greater risk of metastatic disease. Conclusion: Tumour‐associated necrosis is an important prognostic factor for clear cell RCC, independently of WHO/ISUP grade. This supports the suggestion that TAN could be incorporated into tumour grading criteria.